PEMBERDAYAAN KELOMPOK TERNAK UNGGAS BERBASIS BUDIDAYA AYAM BROILER - Emy Saelan; Sariffudin Fatmona; Yunus Syafie (JURNAL PENGABDIAN MANDIRI, 2025)
Empowerment of poultry farming groups based on broiler chicken cultivation in Lalubi Village, East Gane District was carried out with the aim of meeting community demand for fresh chicken meat. In order to improve the skills of farmers in broiler chicken farming efforts, this activity received a positive response from livestock groups in Lalubi Village. The methods used in broiler chicken farming activities include: handling upon arrival of DOC; implementation of vaccination programs; feed management; and training in commercial ration formulation with fermented rice bran. Monitoring and evaluation are carried out periodically and mentoring is carried out continuously to solve every problem faced by the livestock group. The results of the implementation of this community service activity are: the livestock group has knowledge about broiler chicken cultivation including handling when DOC arrives; brooding management; feed processing with fermentation technology; post-harvest handling and marketing of broiler chicken meat